PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS E-LEARNING BAGI GURU SMA NEGARI SATU ATAP WASUR MERAUKE - Martha Loupatty; Izak Habel Wayangkau (Musamus Devotion Journal, 2021)
The Educators are required to always improve their abilities so that they are more competent in terms of mastery communication and information technology. One factor that greatly influences the quality of education is the use of instructional media. Good learning media will help the teachers in organizing a good learning process well and help to improve the student learning outcomes. In an effort to improve teacher professionalism, especially in terms of mastery of technology and information, training is held using computer-based learning applications. The process of activities carried out aims to develop the ability of teachers to utilize existing software in the learning process, improving the abilities of teachers to operate computer usage, and show quantity and quality in various learning process inside and outside the classroom. Service methods used are training in the form of talks, discussions and questions and answers. The training conducted at Satu Atap High School run well and smoothly so that further assistance and development of e-learning media.